Kooperatiflere vergi yolu ile tanınan teşviklerin kooperatifleşmeye etkileri - Dilim, Muzaffer (My University, 1999)
The subject of this research is, The Effects of of the Encouragement's which are provided by Tax to the Cooperatives. Inside of many countries' economical structure, by the public and private sector enter prises. Cooperatives, have the opportunity to get the needs, which people can't get with their own opportunities, by the institutions which are established according to mutual help and cooperation base to get and remove those needs, because ot its contributions to social justice be provided, by its economical benefits. By this way, Cooperatives, are tried to be protected and encouraged with exemptions and exceptions by various law rules, because of the positive contributions of the countries to the economic and social justice, as explained in the theorical of the research. Here, in this research, it's tried to explain the exemptions and exceptions related to the cooperatives which take part in tax laws. These to the cooperatives, to become widespread and be more the activities of the country, by encouraging the activities of the cooperatives which are tended to their economic actions. The factors which wetried to express till now, are determinative at the selection of their research subject. This thesis, of which name is The Effects of the Encouragement's which are given to the Cooperatives to Cooperation has 3 main parts. At the part, it's tried to explain the descry iption, elements, the reasons to establish a cooperative, principles of cooperation, cooperative species, its uses by means of economically and socially, finance, direction organs and audit of the cooperative, by indicating the main conceptions related to the subject. At the part, it's tried to explain the situation of the cooperatives against the tax laws. At the part, the effects of the encouragement's which are given to cooperatives by tax exemptions and exceptions, to cooperation. GİRİŞ Bu çalışmamızın konusu Kooperatiflere Vergi Yolu İle Tanınan Teşviklerin Kooperatifleşmeye Etkileri dir. Bir çok ülkenin ekonomik yapısı içinde kamu ve özel sektör işletmelerin, yanında kooperatif işletmelerinde belirli payı bulunmaktadır. Kooperatifler ekonomik yararların yanında Sosyal adaletin sağlanmasına katkılarından dolayı, bireylerin kendi imkanları ile sağlayamadıkları gereksinmeleri, karşılıklı yardım ve dayanışma esasına göre karşılamak ve gidermek amacı ile oluşturdukları teşekküllerce elde etme imkanına sahip olurlar. Bu bakımdan kooperatifler, Ülkelerin ekonomik ve Sosyal adalet olan olumlu katkılarından dolayı çalışmamızın teorik bölümünde açıklandığı gibi, çeşitli kanun hükümleri ile muafiyet ve istisnalarla korunmaya ve teşvik edilmeye çalışılmıştır. İşte bu çalışmada vergi kanunlarında yer alan kooperatiflerle ilgili muafiyet ve istisnalar açıklanmaya çalışılmıştır. Bu muafiyet ve istisnalar, kooperatiflerin ekonomik hareketlerine yönelik faaliyetlerini teşvik ederek, ülke çapında, yaygınlaşmalarına ve daha verimli olmalarına büyük katkı sağlamaktadır. - Şimdiye kadar anlatmaya çalıştığımız etkenler, çalışma konumuzun seçiminde belirleyici olmuştur. Kooperatiflere vergi yolu ile tanınan teşviklerin kooperatifleşmeye etkileri isimli temizim 3 ana bölümden oluşmaktadır. Birinci bölümde; konu ile ilgili genel kavramlar belirtilerek, kooperatifin tanımı , unsurları, kooperatif kurmanın nedenleri, kooperatifçiliğin ilkeleri, kooperatif türleri, Ekonomik ve sosyal açıdan yararları, Finansman, yönetim organları ve denetimleri, açıklanmaya çalışılmıştır. İkinci bölümde; kooperatiflerin vergi kanunları karşısındaki durumu açıklamaya çalışmıştır. Üçüncü bölümde; kooperatiflere vergi muafiyet ve istisnaları yolu ile tanınan teşviklerin kooperatifleşmeye etkileri açıklanmıştır.
Keywords: Ekonomi; Kooperatifler; KOOPERATİFLER